Primed for Success: The Story of Scientific Design Company How Chemical Engineers Created the Petrochemical Industry - Spitz, Peter H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This is the remarkable story of an entrepreneurial firm that helped to create the petrochemical industry as we know it today. The author also highlights the important role chemical engineers played in developing and commercializing new technologies based on the conversion of hydrocarbons into petrochemicals, which also led to the transfer of technological dominance from Germany to the United States. These developments are illustrated by the participants' personal histories, in the form of interviews and recorded oral histories. In addition, the book presents a highly relevant case study for engineers and managers in the chemical industry. .
The global industry is poised for change -- Fuels and Chemicals Research help win World War II -- Three entrepreneurs join forces -- Conditions are perfect: A new industry grows rapidly -- Scientific Design becomes successful -- The big breakthrough: Mid Century Process -- More inventions: Nylon intermediates, Isoprene, Propylene Oxide -- Other firms: A period of breakthrough inventions -- The leading engineering firm for petrochemicals -- Oxirane and the formation of Halcon International -- A reach too far -- An Ending -- Epilogue.
Keywords: Chemistry, Technical; Strategic planning; Leadership; Chemistry -- History; Chemistry; Technology; History; Industrial Chemistry; Business Strategy and Leadership; History of Chemistry; Chemistry; History of Technology